Interfaces numériques et représentation de soi dans Les Liens artificiels, de Nathan Devers (Revista Cercurilor studenţeşti ale Departamentului de Limba şi Literatura Franceză, 2025)
The purpose of this paper is to analyze the transformations of personal identity in the digital space as depicted in Nathan Devers’ novel Les Liens artificiels. We will follow the identity destruction process of the main character, Julien/Vangel, exploring the factors leading to this “self” decay phenomenon and his reaction to his imminent end. We will also discuss the humanization of the digital apparatus and the instrumentalization and objectification of Julien’s identity; we will address the immersion process into the digital space, identifying the steps and conditions enabling this immersion and the resulting identity transformations. Finally, we will  explore how the character immerses himself in the digital device to the point of total identification, losing his real identity and becoming an integral part of the digital system.